A multi-objective model for multi-product multi-site aggregate production planning in a green supply chain: Considering collection and recycling centers. (July 2016) - Entezaminia, Arezoo; Heydari, Mahdi; Rahmani, Donya
Highlights: Proposing a multi-objective model for a multi-period multi-product multi-site aggregate production planning (APP) problem in a green supply chain. Considering concepts of green and reverse logistics in APP problems. Considering waste management, greenhouse gas (GHG) emissions arising from transportation and production methods to adopt green principles in the model. Maximizing the total score of products in considered environmental criteria quantified by analytical hierarchy process (AHP) methodology as an objective function. Demonstrating the trade-off between the conflicting objective functions by a set of Pareto-optimal solutions generated by the LP-metrics method. Abstract: The present study was designed to incorporate the profit and green principles in an aggregate production planning. It is difficult to ignore the key role of green principles in balancing environmental and economic performance for companies facing community, and competitive pressures. In this paper, a multi-objective multi-period multi-product multi-site aggregate production planning (APP) model is presented in a green supply chain considering a reverse logistic (RL) network. In the proposed model, products are scored in terms of environmental criteria such as recyclability, biodegradability, energy consumption and product risk, using analytical hierarchy process (AHP). Speaking in simple terms, the AHP concept is utilized to get one single indicator that describes environmental impact of various production alternatives. Some other green indicators including waste management, greenhouse gas (GHG) emissions arising from production methods and transportation are embedded in the model. The limited number of potential collection and recycling centers can be opened in order to produce the second-class goods. The LP-metrics method is used to consider two conflicting objectives, i.e. minimizing total losses and maximizing total environmental scores of products, simultaneously. Further, the trade-off between objectives is demonstrated by a collection of Pareto-optimal solutions. The model shows how profit and green principles can be incorporated in an APP problem. Finally, the model validity is demonstrated by a numerical example. The sensitivity analysis is carried out for GHG emission level arising from production and transportation and industrial waste level to provide some useful managerial insights, then analysis of the cost and profit in collection and recycling system, is conducted to show its performance.